1982
DOI: 10.1002/1520-6866(1990)2:1<31::aid-tcm1770020105>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of inhibited cell-cell communication in teratogenesis

Abstract: A mechanistic link between teratogenesis and carcinogenesis has been suggested by a wide variety of scientific observations. This report attempts to provide a theoretical explanation for one of the several possible mechanisms which might be shared during carcinogenesis and teratogenesis. The initiation and promotion concept of carcinogenesis was briefly reviewed and the role of intercellular communication during the complex tumor promotion phase was discussed. Inhibition of intercellular communication by a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 106 publications
0
22
0
Order By: Relevance
“…Trosko et al (13) proposed a hypothesis that teratogenesis and tumor promotion may share for this idea is lent by teratology studies which found that exposure to EGME and EGEE significantly lengthened gestation in rats and mice (22,23). Since labor is dependent upon the formation of gap junctions between the myometrial cells (4), increased length of parturition might be a sign of gap junction interference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trosko et al (13) proposed a hypothesis that teratogenesis and tumor promotion may share for this idea is lent by teratology studies which found that exposure to EGME and EGEE significantly lengthened gestation in rats and mice (22,23). Since labor is dependent upon the formation of gap junctions between the myometrial cells (4), increased length of parturition might be a sign of gap junction interference.…”
Section: Discussionmentioning
confidence: 99%
“…Pools of small metabolites (1000 to 1500 daltons, depending upon configuration) are also shared among cells joined by gap junctions (2 This assay has been widely applied to identify tumor promoters (11,12) and was recently proposed as an assay for teratogens (13). The assay was employed in the present study of ethylene glycol (EG) and some structurally related monoalkyl glycol ethers since some of these compounds have recently been found to be teratogenic in laboratory animals (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…There appears to be a link between teratogenicity and carcinogenesis, in that many carcinogenic compounds are also teratogenic in nature, whereas teratogenic compounds are not necessarily implied to be carcinogenic (Trosko et al, 1982). The compounds which stimulate GJIC, such as retinoic acid and vitamin D, can also suppress tumour formation (Tanmahasamut and Sidell, 2005).…”
Section: The Relation Between Gap Junction Intercellular Communicatiomentioning
confidence: 99%
“…Trosko and co-workers (7) found that a variety of chemicals have the ability to increase the recovery of mutant 6-TGr cells when co-cultured with wild-type 6 24 hr, at which time the medium is replaced with or without the test compound. The HEPM cells are then maintained in culture for an additional 72 hr.…”
Section: Critical Reviewmentioning
confidence: 99%